Cultural issues in end-of-life decision making - Braun, Kathryn; Pietsch, James H.; Blanchette, Patricia L.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2000)
The difficult decisions that face dying individuals, their families and the professionals that help them at the end of their life are impacted by cultural background, religious upbringing, education and experience.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Death -- Social aspects -- United States; Terminal care -- United States; Minorities -- Medical care -- United States; Electronic books